Effects of potassium chloride on microbiological and sensory characteristics of frozen pork tocino - Cadapan, Lumen Tribo (2002., 2002)
ABSTRACT The quality stability during freezing storage of pork tocino with potassium chloride (KCl) as a substitute to sodium chloride (NaCl) was determined. Selection of standardized cooking procedure was done using varied frying time: 6, 7, and 8 minutes respectively. Data showed that pork tocino cooked with 7 minutes frying time was the most preferred. The most acceptable 66.7% KCl level (modified from BAI's formulation) from Madrio's (UP-CHE, 2000) study was used for experimentation. Standard cooking procedure was selected, and the 7 minutes frying time was found to be ideal. Two formulations (100% NaCl and 66.7 KCl : 33.3 NaCl) of pork tocino were produced and stored for one month under freezing conditions. Microbial examination revealed that KCl can be an effective inhibitory for growth of microorganisms. Total plate and coliform counts (<10 cfu/ml) passed BFAD standards. Staphylococcus sp. showed results within standards only (<10 cfu/ml) on day1, day 22, and day 29 of storage. Inconsistencies in results for presence of Staphylococcus may be accounted to some flaws in the experimentation phase. To further determine effects of KCl substitution in frozen pork tocino, sensory testing was done. Tocino samples were still acceptable, in terms of overall acceptability, color, flavor, juiciness, saltiness, texture, and off-flavor) after one month storage. Results indicated that replacement of KCl in frozen pork tocino preserves product's microbial and sensory qualities. Data obtained from the control and the KCl treated samples were comparatively not significantly different at 5% level of confidence. Hence, this research is conclusive that KCl can be practically be used as a substitute to sodium chloride in the production of pork tocino.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat -- Preservation; Preservatives